2022
DOI: 10.1088/2053-1591/ac4627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle grading composition of SiC on properties of silicon-bonded SiC porous ceramics

Abstract: Silicon-bonded silicon carbide (SBSC) porous ceramics had been prepared by mixing two different particle size of SiC powder (coarse and fine) as aggregates for silicon carbide porous ceramics, adding metallic Si as the binder phase and firing at 1450 °C under argon atmosphere. Various combinations of SiC mixtures consisting of two different particle size and packing density were prepared, and the samples were investigated to understand apparent porosity, bending strength, pore size distribution, and microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The reason for choosing these two parameters is to ensure the density of the sample after printing. For photocuring printing technology, high solid content and finer powder are helpful to improve the various physical properties of the final product [ 24 , 25 ]. Copper powder’s particle size distribution and morphology were measured by a laser particle sizer (Winner 2000, Jinan Micro-Nano Particle Instrument Co., Ltd., Jinan, China) and a scanning electronic microscope (Phenom Pro, Phenom-World, Eindhoven, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…The reason for choosing these two parameters is to ensure the density of the sample after printing. For photocuring printing technology, high solid content and finer powder are helpful to improve the various physical properties of the final product [ 24 , 25 ]. Copper powder’s particle size distribution and morphology were measured by a laser particle sizer (Winner 2000, Jinan Micro-Nano Particle Instrument Co., Ltd., Jinan, China) and a scanning electronic microscope (Phenom Pro, Phenom-World, Eindhoven, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…However, brittleness restricts the development and application of ceramic materials. After a lot of research, researchers found that adding an appropriate amount of whiskers to ceramic materials is one of the effective ways to overcome brittleness and improve toughness [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%